Comme si Nous Attrapions un Cobra - Alabdalla, Hala (France, 2012)
Cartoonists’ words and art embody the democratic aspirations of people in the Arab world as it undergoes revolutionary upheaval. This film is an attempt to contribute to a form of universal resistance.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films